PENGARUH PENDIDIKAN KESEHATAN DENGAN AUDIO VISUAL TERHADAP PERILAKU PENCEGAHAN PENULARAN PADAKELUARGA DENGAN TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS SIKUMANA - sisilia bili (CHMK HEALTH JOURNAL, 2019)
Tuberculosis is a disease caused by the bacterium Mycobacterium tuberculosis that is usually transmitted through droplets when people are talking, coughing, or sneezing, so that the risk of spreading to the other family members dramatically increase. Family’s behavior in preventing the transmission of TB needs to be improved through health education involving audio-visual. This research aims to analyze the effect of health education using audio-visual to family behavior in order to prevent the transmission of Tuberculosis. The research design is quasy-experimental design using a pre-post test with control group. The sampling technique used is simple random sampling with a sample of 56 respondents. Data is collected by using questionnaire sheet. Based on the test results of non-parametric Wilcoxon statistics, indicating that the domain knowledge p value = 0.000, 0.046 and 0.003 gauge attitudes domain (α = 0.05). The results of this statistical test proves that health education on the prevention of transmission by using audio-visual influence the family’s behavior to minimize the possibility of behavior in families with pulmonary tuberculosis in Sikumana Public Health Center. The advantage of the audio-visual media can increase the knowledge, attitude and practice of family until three times to prevent the transmission of Pulmonary Tuberculosis. This is expected to continue to motivate health workers and provide health education with a more attractive media such as audio-visual media for families with Pulmonary Tuberculosis, particularly about the behavior of Pulmonary Tuberculosis prevention of transmission. Keywords: Audio Visual, Behavior, Tuberculosis